Pakistan’s Participation in the War on Terror and US Concerns: An Analysis - Ishrat Afshan Abbasi (JISR Management and Social Sciences & Economics, 2013)
Pakistan was selected as a frontline state in the US-led war against terrorism for two, fundamental reasons: at instant, the US wanted to isolate Afghanistan and Taliban breaking its alliance with Pakistan and the second reason was Pakistan’s geostrategic position to make this war favorable for US from several perspectives. Whereas for Pakistan this participation was based on a three-pronged strategy: firstly, to avoid the wrath of the US; secondly, to make the best use of this opportunity for economic benefits; and thirdly, to thwart all Indian propagandas to postulate Pakistan as a sponsor of extremism and terrorism. This article explores the backdrop of Pakistan’s major interests in the war on terror and the ground realities related to its participation. It also discusses the major concerns of the US regarding Pakistan’s performance in this war. In addition, this article addresses the questions about weaknesses and loopholes of this war due to which Pakistan is still entangled in this endless action beyond the decade.